Differences in the morphological and productive characteristics of Nicotiana tabacum L. tobacco leaves according to their location on the plant (Journal of Hama University, 2025)
The research was carried out at the Tobacco Research Center of the General Tobacco Corporation in Rumaila - Jableh – Lattakia, Seeds of the tobacco variety (Jeb Hassan) were planted to study the effect of leaf location on the stem on some morphological and production characteristics by collecting the leaves according to four picks, first, second, third and fourth.The results showed variation in morphological characteristics (length, width, leaf area  Length / Width ratio) and productivity in addition to leaf material and thickness among the four harvest. The leaves of the first and second harvests gave the best results, with leaf length (27.8 and 24.9 cm), leaf width (16.4 and 14.2 cm), andleaf area (312.33 and 241.49 cm2), The productivity of green leaves reached (545 and 303 g), dry leaves (80.25 and 72.25 g), and the net percentage reached (13.44 and 20.55%), While the leaf material recorded the best values ​​in the fourth harvest (69.88 g/cm2), as well as the thickness (89.61 microns) and the Length / Width ratio (1.95).                                                                                    The leaves of the first and second harvests gave the best values ​​for morphological and productive specifications compared to the third and fourth harvests, While the values ​​of the manufacturing technological data were the best in the third and fourth harvests.
Keywords: Keywords: Nicotiana tabacum- Yield- Length / Width ratio- leaf material- leaf area.